2004
DOI: 10.1080/10937400490258873
|View full text |Cite
|
Sign up to set email alerts
|

Avian Immunotoxicology

Abstract: Methods for studying the avian immune system have matured during the past two decades, with laboratory studies predominating in earlier years and field studies being conducted only in the past decade. One application has been to determine the potential for environmental contaminants to produce immune suppression, while another research direction is looking at the evolutionary significance of a robust immune system, and the relationship between immune competence and fitness parameters. Laboratory studies of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 171 publications
(198 reference statements)
0
93
0
7
Order By: Relevance
“…In this respect, the in vitro lymphocyte proliferation assay used here is a good option for assessment of adaptive immunity because it can be performed with a single small blood sample collected in the field and measures important aspects of acquired immune responses, that is, the ability of lymphocytes to become activated and proliferate upon challenge. Using different mitogens (e.g., PHA, ConA, LPS), different lymphocyte subsets are targeted, providing information on more than one cell type (Fairbrother et al 2004). Although performance of this assay requires a specialized laboratory setting, it can be accomplished through fruitful collaborations among ecoimmunologists and more traditional immunologists, as is generally the case for other measures of immune function (e.g., Matson et al 2005Matson et al , 2006Millet et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, the in vitro lymphocyte proliferation assay used here is a good option for assessment of adaptive immunity because it can be performed with a single small blood sample collected in the field and measures important aspects of acquired immune responses, that is, the ability of lymphocytes to become activated and proliferate upon challenge. Using different mitogens (e.g., PHA, ConA, LPS), different lymphocyte subsets are targeted, providing information on more than one cell type (Fairbrother et al 2004). Although performance of this assay requires a specialized laboratory setting, it can be accomplished through fruitful collaborations among ecoimmunologists and more traditional immunologists, as is generally the case for other measures of immune function (e.g., Matson et al 2005Matson et al , 2006Millet et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although performance of this assay requires a specialized laboratory setting, it can be accomplished through fruitful collaborations among ecoimmunologists and more traditional immunologists, as is generally the case for other measures of immune function (e.g., Matson et al 2005Matson et al , 2006Millet et al 2007). The lymphocyte proliferation assayas do most assays of immune function-has some limitations in addition to its strengths (Fairbrother et al 2004;Demas et al 2011). In particular, this assay assesses only early steps of acquired immune responses; thus, for a more complete assessment of acquired immunity of animals that cannot be easily recaptured in the wild, additional in vitro assays that measure effector functions such as B-cell antibody production or T-cell cytotoxicity and that also involve a single blood sample could be performed (Fairbrother et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Simon et al (2003) recently showed that Protocalliphora larvae aggregate on the smallest chicks of a brood, which tend to be less immunocompetent than their siblings (Christe et al, 1998). Several environmen-tal contaminants are known to affect the immune system of wildlife (reviewed by Fairbrother et al, 2004). If chemicals present in OPSM were affecting the immune function of nestlings, perhaps parasitic larvae feeding on those nestlings would have greater survival rates than those developing on chicks with normal immune defenses, partly explaining the larger parasitic loads on reclaimed sites.…”
Section: Blow Flies On Ospm Sites: Host Characteristicsmentioning
confidence: 99%
“…IgM, IgG, IgA and IgY antibodies have been described in birds, but identical roles to mammalian forms have not been confirmed. In avian studies, common measures of in vivo immune function are the phytohemagglutinin (PHA) skin test response and antibody response to foreign red blood cells (Fairbrother et al 2004). The PHA skin test is a T-cell-dependent inflammatory response.…”
Section: Avian Immunologymentioning
confidence: 99%